Mass spectrometry quantification of beef and pork meat in highly processed food: Application on Bolognese sauce. (April 2017) - Prandi, Barbara; Lambertini, Francesca; Faccini, Andrea; Suman, Michele; Leporati, Andrea; Tedeschi, Tullia; Sforza, Stefano
Abstract: Food frauds have become a very important issue in the field of food quality and safety. The risk of food adulteration is higher in highly processed food and mainly affects high added value foodstuff. The methods currently available to face this issue, PCR and ELISA, are very sensitive and specific, but they have some limitations. In the present work, tandem mass spectrometry is presented as an emerging approach to detect beef and pork meat in very complex and highly processed food matrices, such as Bolognese sauce, both in qualitative than in quantitative way. The detection is achieved using two different marker peptides, specific for beef and pork meat, both deriving from α2-collagen chain. Then, a calibration curve is set up using real sauces made by different percentages of pork and beef meat in a working range from 0 to 100%. The method here developed allows to quantify beef and pork meat in a complex product such as Bolognese sauce. Highlights: Myofibrillar proteins were extracted from Bolognese sauce and submitted to tryptic digestion. Marker peptides for beef and pork meat were identified using LC-MS/MS. Calibration curves were constructed at different beef and pork percentages in the sauce. The method was accurate in detecting beef and pork amount in blind samples.